Human rights of migrants and refugees. (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2025)
The present work addresses the issue of the human rights of immigrants and refugees” in various borders of the world facing a series of challenges and particular situations depending on the country, as well as the national and regional context. Borders represent critical points where the human rights of immigrants are often violated due to restrictive policies, lack of adequate resources for protection, and practices of prolonged or arbitrary detention. International human rights organizations and humanitarian agencies work to ensure that the rights of immigrants are respected and protected at all stages of their migratory journey until the end of their journey. The problem is addressed, in these years there were vulnerabilities to the rights of immigrants, from disappearances, human trafficking, rapes, assaults, deportation, among others, several people even lost their lives during their transfer. This work analyzes the human rights of immigrants and refugees. However, the effective implementation of these rights often faces challenges due to factors such as lack of resources, restrictive policies of some countries, and xenophobia.
Keywords: Immigrant; human rights; borders, refugees; xenophobia